1992
DOI: 10.1016/0014-5793(92)80308-4
|View full text |Cite
|
Sign up to set email alerts
|

Different regulation of collagen I gene transcription in three‐dimensional lattice cultures

Abstract: Human skin fibroblasts were cultivated in confluent monolayers, retracting collagen lattices. retracting fibrin lattices and non-retracting fibrin lattices and the expression of messcngcr RNA specific for the a, chain of type I procollagen comparatively studied by Northern blot and dot blot hybridization. Two factors contribute to the lower level or procollagen messenger RNA in collagen lattices: the retraction and the nature of the fibrillar protein that constitutes the lattices. Fibrin lattices, when they do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…This general mechanism does not rule out the involvement of other mechanisms already demonstrated, and particularly the transcriptional regulation of various genes [7], some of them being down-regulated and other up-regulated. However, this overall regulation of fibroblast metabolism should account for a great part of the modifications noticed in this type of cultures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This general mechanism does not rule out the involvement of other mechanisms already demonstrated, and particularly the transcriptional regulation of various genes [7], some of them being down-regulated and other up-regulated. However, this overall regulation of fibroblast metabolism should account for a great part of the modifications noticed in this type of cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case particularly for the type I collagen gene [7], However, the overall decrease of protein synthesis suggests that more general mechanisms are involved.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They also demonstrated that this effect is only partly due to the enhancement of collagen density. Gillery et al 39 demonstrated that the retraction and the nature of the fibrillar protein that constitutes the lattices contribute to the lower level of procollagen mRNA in collagen lattice-cultured fibroblasts. Unemori and Werb 40 report that the stimulation of collagenase synthesis in fibroblasts within a collagen gel does not occur if contraction of the gel is inhibited by mechanical means.…”
Section: Discussionmentioning
confidence: 99%